Chaotic lidar - Lin, F.-Y.; Liu, J.-M. (IEEE journal of selected topics in quantum electronics, 2004)
A novel chaotic lidar (CLIDAR) system that utilizes a chaotic laser as the light source is proposed and studied. In CLIDAR, the detection and ranging are realized by correlating the signal waveform reflected back from the target with a delayed reference waveform. Benefiting from the very broad bandwidth of the chaotic waveform that can be easily generated by a semiconductor laser, a centimeter-range resolution is readily achieved. The correlation performance of CLIDAR is studied both numerically and experimentally. The power spectra, phase portraits, time series, and correlation traces of the chaotic waveforms obtained at different operating conditions are compared. The relation between the complexity of the attractor and the correlation property is examined. The correlation dimension and the largest positive Lyapunov exponent of each waveform are calculated. To compare the correlation performance of the waveforms quantitatively, peak sidelobe levels of the correlation traces with different correlation lengths and relative noise levels are investigated. Preliminary experiments show a subcentimeter accuracy in ranging with a 3-cm-range resolution, which currently is limited by the bandwidth of the oscilloscope used.